Help-Seeking Behaviors and Barriers Among Black Women Exposed to Severe Intimate Partner Violence: Findings From a Nationally Representative Sample - Lacey, Krim K. (Violence against women, 2021)
This article examined general help-seeking utilization and barriers among U.S. Black women reporting severe physical intimate partner violence (IPV). Data from the National Survey of American Life (NSAL), the largest and most detailed survey on Blacks residing in the United States, were analyzed. Among U.S. Black women reporting severe physical IPV, many sought the help of a psychiatrist (13.8%) or other mental health professionals (14.0%). Multivariate findings revealed associations between help-seeking utilization and sociodemographic factors. Queries from open responses suggested potential cultural and ethnic differences between African American and Caribbean Black women reporting intimate partner violence in relation to barriers to help-seeking.